Teaching webside manner: development and initial evaluation of a video consultation skills training module for undergraduate medical students. Issue 1 (1st January 2021) - Gunner, Charlotte K.; Eisner, Emily; Watson, Angus JM; Duncan, John L.
ABSTRACT: Background: Video consultations are increasingly used to communicate with patients, particularly during the current COVID-19 pandemic. However, training in video consultation skills receives scant attention in the literature. We sought to introduce this important topic to our undergraduate medical school curriculum. Objective: To increase final year medical students' video consultation skills and knowledge. Methods: We used Plan, Do, Study, Act (PDSA) quality improvement methodology with a pre-post study design to develop a teaching session for 5th year medical students, informed by a literature review and online clinician survey. The 2 hour session comprised an introduction and three practical stations: patient selection and ethics, technology and example videos, and simulation. Subjective pre- and post-session confidence was reported by students across seven domains using 5-point scales (1: not at all confident; 5: extremely confident). Students and facilitators completed post-session feedback forms. Results: The 40 students and 3 facilitators who attended, over two separate teaching sessions, provided unanimously positive feedback. All students considered the session relevant. Subjective confidence ratings (n = 34) significantly increased from pre- to post-session (mean increase 1.78, p < 0.001). Conclusions: The inaugural teaching session was well-received and subjective assessment measures showed improvement in taught skills. This pilot has informed a UK-wide multi-centre study with subjective and objective data collection.